Pengaruh Penggunaan Atlas Elektronik Terhadap Hasil Belajar Geografi di SMA Labschool Jakarta - Rahardjo, Eko Tri (Parameter, 2019)
Abstract This study aims to get practical answers about the effect of the use of electronic atlases on student learning outcomes in class XI on geography subjects. Research using experimental methods. The population in this study were all students of class XI Labschool Jakarta High School. The sampling technique used is purposive sampling, where one class is an experimental class taught by using an electronic atlas, and another type as a comparison class that is a control class taught not to use an electronic atlas. The instrument used in this study was in the form of multiple-choice tests namely pre-test and post-test. The data analysis technique used to test hypotheses is the t-test. The results showed that there were differences in student learning outcomes between the experimental class and the control class on natural resource material. Before conducting the hypothesis test, the data requirements test is carried out, namely data normality test using Chi-Square test and data homogeneity test using Bartlet test. From the results of normality test data both pre-test and post-test in the experimental class and the control class obtained prices X2-count < X2-table, meaning that the data collected are typically distributed. The results of the homogeneity test data calculations using the Bartlet test also obtained estimates F2-count < F2-table, eaning that the data from both groups are homogeneous. After testing the data requirements, a hypothesis test is performed using the t-test, and values are obtained t-count = 3,61 dan t-table with dk 56, and the 0.05 significance level is 1.67. So t-count > t-table means that the alternative hypothesis is accepted, and the null hypothesis is rejected. The results of the study concluded that there is an influence of the use of electronic atlases on the learning outcomes of students of class XI IPS on geography subjects with natural resource material. Therefore, geography study teachers can use this electronic atlas as one of the media used in the learning process of geography. Keywords: Electronic atlas, Geography learning outcomes, Labschool High School Jakarta Abstrak Penelitian ini bertujuan untuk mendapatkan jawaban empiris mengenai pengaruh penggunaan atlas elektronik terhadap hasil belajar siswa kelas XI pada mata pelajaran geografi. Penelitian menggunakan metode eksperimen. Populasi dalam penelitian ini adalah semua siswa kelas XI SMA Labschool Jakarta. Teknik pengambilan sampel yang digunakan yaitu purposive sampling, dimana satu kelas merupakan kelas eksperimen yang diajarkan dengan menggunakan atlas elektronik dan satu kelas lagi sebagai kelas pembanding yaitu kelas kontrol yang diajarkan tidak menggunakan atlas elektronik. Instrumen yang digunakan dalam penelitian ini adalah dalam bentuk tes pilihan ganda yaitu pre-tes dan post-tes. Teknik analisa data yang digunakan untuk menguji hipotesis adalah Uji-t. Hasil penelitian menunjukkan bahwa terdapat perbedaan hasil belajar siswa antara kelas eksperimen dan kelas kontrol pada materi sumber daya alam. Sebelum melakukan uji hipotesis terlebih dahulu dilakukan uji persyaratan data yaitu uji normalitas data dengan menggunakan uji Chi Kuadrat dan uji homogenitas data dengan menggunakan uji Bartlet. Dari hasil uji normalitas data baik pre-tes maupun post-tes pada kelas eksperimen dan kelas kontrol diperoleh harga X2-hitung < X2-tabel, artinya data yang diperoleh berdistribusi normal. Hasil perhitungan uji homogenitas data dengan menggunakan uji Bartlet juga diperoleh harga F2-hitung < F2-tabel, artinya data dari kedua kelompok tersebut bersifat homogen. Setelah melakukan uji persyaratan data, kemudian dilakukan uji hipotesis dengan menggunakan uji-t dan diperoleh nilai t-hitung = 3,61 dan t-tabel dengan dk 56 dan taraf signifikansi 0,05 adalah 1,67. Jadi t-hitung > t-tabel artinya hipotesis alternatif diterima dan hipotesis nol ditolak. Hasil penelitian menyimpulkan bahwa terdapat pengaruh penggunaan atlas elektronik terhadap hasil belajar siswa kelas XI IPS pada mata pelajaran geografi dengan materi sumber daya alam. Oleh karena itu guru bidang studi geografi dapat menggunakan atlas elektronik ini sebagai salah satu media yang digunakan dalam proses belajar mengajar geografi. Kata kunci: Atlas elektronik, Hasil belajar Geografi, SMA Labschool Jakarta